Les champs électriques et magnétiques : l’impact sur l’assurance - Moreau, Rémi (Assurances, 1995)
The debate is heating up. Does exposure to Electromagnetic Fields (EMF) present health risks? In the United States and Canada, there is a growing body of literature and studies that point to the dangers of EMF, while certain parties argue that the findings are inconclusive. This article presents an overview of the EMF controversy and its impact on the insurance and reinsurance industry.